Contributing to the breeding phenology of a temperate nocturnal gecko - Michel-Jean Delaugerre (Acta Herpetologica, 2025)
This short descriptive note updates and summarises knowledge on the breeding phenology of the nocturnal Gekkota Euleptes europaea. A forty-year dataset covering the entire range of the species is provided. Between 1982 and 2024, a total of 39 populations were studied in 85 sampling sessions. Reproduction is highly seasonal, with gravid females appearing from early spring until mid-June when oviposition begins. Hatching occurs from mid-August to early October. This study and the dataset provided will allow further work to assess whether, and to what extent, climate change would affect the breeding phenology of this nocturnal gecko.